2003
DOI: 10.1002/ijc.10909
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated PTEN‐PKB and negative receptor status in human breast cancer

Abstract: Recent studies demonstrate that abnormalities in PTEN may be one of the most frequent genetic events observed in human cancers. PTEN dysfunction leads to tumorigenesis through unopposed survival signals mediated via activated protein kinase B (PKB), which may also be associated with hormone-independence. We therefore investigated the relationship between PTEN-PKB and receptor status in human breast cancer. Several molecular variables, including immunohistochemical staining for PTEN, PKB (phosphorylated on ser4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 56 publications
10
59
1
1
Order By: Relevance
“…Furthermore, ER and PR were still expressed in four of the five tumors that had lost the wild-type Pten allele (Figure 3a and b). These results suggest that loss of Pten does not prevent ER expression in mammary cancers, consistent with another study examining ER expression in mammary lesions in Pten þ /À mice that do not carry a transgene (Shi et al, 2003). Neu (HER2, ErbB2) is a member of the epidermal growth factor receptor (EGFR) family of transmembrane tyrosine kinases (Olayioye et al, 2000).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, ER and PR were still expressed in four of the five tumors that had lost the wild-type Pten allele (Figure 3a and b). These results suggest that loss of Pten does not prevent ER expression in mammary cancers, consistent with another study examining ER expression in mammary lesions in Pten þ /À mice that do not carry a transgene (Shi et al, 2003). Neu (HER2, ErbB2) is a member of the epidermal growth factor receptor (EGFR) family of transmembrane tyrosine kinases (Olayioye et al, 2000).…”
Section: Resultssupporting
confidence: 85%
“…Loss of Pten is usually associated with ER À human breast cancers (Garcia et al, 1999;Perren et al, 1999;Shi et al, 2003). We have previously reported that inactivation of one allele of Pten accelerates mammary tumorigenesis in MMTV-Wnt-1 TG mice, and 70% of the resulting tumors have lost the wild-type allele of Pten (Li et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…PTEN (phosphatase and tensin homologue deleted on chromosome 10) inhibits PKB activation by virtue of its dephosphorylating role in reverting PIP 3 to PIP 2 . We and others have documented that PTEN is underexpressed in approximately 30% of human breast cancers, 27,28 resulting in upregulation of PKB activity, which in turn is associated with reduced patient survival. 29 Hyperthermia has been demonstrated in Phase III randomized trials to benefit patients with both improved local control 1,4,5 and survival.…”
Section: Discussionmentioning
confidence: 90%
“…One possible explanation might be related to the endogenous PTEN-PKB pathway whereby we have previously documented that the more sensitive MDA-MB-468 cells lack PTEN and have increased P-PKB expression. 27 In contrast, the MCF-7 cells have preserved PTEN expression, and undetectable phospho-PKB (in the unstimulated state). Hence, potentially, the MDA-MB-468 cells may be dependent upon activated PKB for their continued proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation